ROSENTHAL, Eric Inventory of documents - ROSENTHAL, Eric (ARCA, 2018)
Private papers of Eric Rosenthal, author, journalist and broadcaster.
COVERAGE 1904; 1 File; 011 metre.
Keywords: ROSENTHAL, Eric; Journalist